Development of an Integrated Curriculum Based on the Pyramid of Learning in Improving Student Learning Activities at the Darul Ma’arif Surakarta Integrated Islamic Elementary School - Supriyanto, Joko (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
This study aims to describe and reveal the foundation, management and impact of implementing an integrated curriculum based on the Pyramid of Learning at the Darul Ma’arif Integrated Islamic Elementary School. This research uses a qualitative approach, the type of research is descriptive using a case study model design. The data collection techniques were obtained based on the results of observations, interviews and documentation. Checking the validity of the data using triangulation. This study found the following: (1) The foundation for implementing an integrated curriculum based on the Pyramid of learning is the foundation of religion, philosophy, psychology, social and culture, and science and technology (2) Curriculum management includes planning, implementation and evaluation starting with designing , carry out and evaluate observation activities, learning activities, stimulation activities, and habituation activities. (3) The impact of applying the Pyramid-based curriculum of learning is to make students’ knowledge more meaningful, students read with understanding, students are independent in everyday life, students’ emotions are stable so that they are ready to accept learning well, and make students’ abilities run according to completeness stages and development.